A pragmatic randomized controlled trial of the Flinders Program of chronic condition management in community health care services. Issue 11 (November 2015) - Battersby, Malcolm; Harris, Melanie; Smith, David; Reed, Richard; Woodman, Richard
Highlights The Flinders Program improved quality of life in a range of chronic conditions. The Partners In Health scale can be used to measure chronic disease self-management. In-practice delivery of self-management and coordination programs appears inadequate. Better quality of delivery is needed so patients can benefit from such programs.